2018
DOI: 10.3390/nu10010097
|View full text |Cite
|
Sign up to set email alerts
|

Specific Collagen Peptides Improve Bone Mineral Density and Bone Markers in Postmenopausal Women—A Randomized Controlled Study

Abstract: Introduction: Investigations in rodents as well as in vitro experiments have suggested an anabolic influence of specific collagen peptides (SCP) on bone formation and bone mineral density (BMD). The goal of the study was to investigate the effect of 12-month daily oral administration of 5 g SCP vs. placebo (CG: control group) on BMD in postmenopausal women with primary, age-related reduction in BMD. Methods: 131 women were enrolled in this randomized, placebo-controlled double-blinded investigation. The primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 31 publications
1
71
0
2
Order By: Relevance
“…Furthermore, daily oral administration of 5 g of a collagen-hydrolysate food product (containing 0.1 or 2 g Pro-Hyp and Hyp-Gly per kg product) by 35-55 year-old women for 8 weeks resulted in dose-dependent improvements in facial skin conditions, such as skin moisture, elasticity, wrinkles, and roughness (Inoue et al 2016). Of particular interest, 12-month daily oral administration of 5 g collagen hydrolysates (containing 4-hydroxyproline) augmented bone mineral density in postmenopausal women (König et al 2018), suggesting their role in preventing osteoporosis. Similarly, dietary supplementation with 4-hydroxyproline-containing collagen hydrolysates (10 g/day) in combination with calcitonin for 24 weeks has shown positive effects on mitigating osteoporosis in postmenopausal women (Adam et al 1996).…”
Section: Health Benefits Of 4-hydroxyproline Supplementationmentioning
confidence: 99%
“…Furthermore, daily oral administration of 5 g of a collagen-hydrolysate food product (containing 0.1 or 2 g Pro-Hyp and Hyp-Gly per kg product) by 35-55 year-old women for 8 weeks resulted in dose-dependent improvements in facial skin conditions, such as skin moisture, elasticity, wrinkles, and roughness (Inoue et al 2016). Of particular interest, 12-month daily oral administration of 5 g collagen hydrolysates (containing 4-hydroxyproline) augmented bone mineral density in postmenopausal women (König et al 2018), suggesting their role in preventing osteoporosis. Similarly, dietary supplementation with 4-hydroxyproline-containing collagen hydrolysates (10 g/day) in combination with calcitonin for 24 weeks has shown positive effects on mitigating osteoporosis in postmenopausal women (Adam et al 1996).…”
Section: Health Benefits Of 4-hydroxyproline Supplementationmentioning
confidence: 99%
“…Besides, CHs from pig or deer also exerted significant effects on preventing bone loss, improving BMD, and increasing histomorphometric parameters and mechanical indicators in OVX animal models [ 15 , 16 ]. Clinical trials further demonstrated that special collagen peptides improved BMD and bone markers in postmenopausal women [ 17 ]. However, previous investigations mainly focused on studying the effect of mammalian or bone CHs on osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of ageing, post-menopausal females supplemented with 5 g/d calcium-collagen chelate (albeit with 500 mg calcium and 200 IU vitamin D 3 ) for 12 months had attenuated whole-body BMD losses compared to control (calcium and vitamin D 3 ) [140]. Whilst these positive effects cannot necessarily be attributed purely to collagen supplementation due to insufficient dietary control, these findings were later echoed by a 12-month randomised, double-blind, placebo-controlled trial, in which postmenopausal females given 5 g/d collagen peptide demonstrated significant increases in BMD of the femoral neck and lumbar spine and an increase in P1NP, indicative of an increase in bone formation [141]. Expectedly, the control group (5 g/d maltodextrin) displayed numerical (non-significant) declines in BMD and increases in CTX, indicative of bone degradation over the intervention period [141].…”
Section: Bonementioning
confidence: 99%
“…Whilst these positive effects cannot necessarily be attributed purely to collagen supplementation due to insufficient dietary control, these findings were later echoed by a 12-month randomised, double-blind, placebo-controlled trial, in which postmenopausal females given 5 g/d collagen peptide demonstrated significant increases in BMD of the femoral neck and lumbar spine and an increase in P1NP, indicative of an increase in bone formation [141]. Expectedly, the control group (5 g/d maltodextrin) displayed numerical (non-significant) declines in BMD and increases in CTX, indicative of bone degradation over the intervention period [141]. Since there were no differences in macro-or micro-nutrient intake observed between the treatment and control groups pre-or post-intervention, this may indicate that the positive effects on BMD are attributable to collagen supplementation.…”
Section: Bonementioning
confidence: 99%